Training Social Care Workers for Implementing Health Protection Technologies in the Pedagogical Process of Nursery Schools - Surzhanska, Viktoriya Anatoliyivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Introduction. The human life has always been the highest value of humanity and health. The importance of healthcare from the birth and through the life was pointed out in the Ukrainian folklore. The national policy of Ukraine determines the significance of forming healthy lifestyle and healthcare of pre-schoolers in numerous normative documents, including the Law of Ukraine “About Education”, the National Doctrine of Development of Ukraine in the twenty-first century, the Law of Ukraine “About Pre-School Education”, Basic Component of Pre-School Education in Ukraine. The requirements for competence level of children concerning the issue of healthcare are defined in The Basic Component. To gain the necessary competences is the task of not only parents, but also of nursery school staff such as nursery school counsellors and teachers, music and physical education teachers as well as social pedagogues. Purpose. To define the peculiarities of future social care workers training to provide children healthcare technologies in the pedagogical process of nursery schools. Methods. Generalization, analysis of scientific works, normative documents, curricula and studying programmes of disciplines and practices at higher educational establishments. Results. The competences of pre-schoolers in the educational direction «The Personality of a Child» concerning health was defined on the basis of the analysis of normative documents and scientific sources. The researches of the issues of forming healthy lifestyles and healthcare technologies of pre-school and primary school children in the educational process are analyzed. Originality. The author’s original interpretation of the peculiarities of the future social care workers training to the implementation of children healthcare technologies in the educational process of nursery schools is offered. Conclusion. The peculiarities of future social care workers training to the implementation of children healthcare technologies in the educational process of nursery schools are revealed in the article. 1) The described training is organized with taking into account tasks and obligations of social pedagogues, that are listed in the qualification characteristics of the profession. 2) Nowadays the training is organized locally and requires further detailed planning. 3) The introduction of healthcare technologies to future social care workers takes place within an integral educational system being it’s specific feature with certain components. 4) The implementation of healthcare technologies is closely connected with the use of other technologies that protect health of all the participants of the educational process. 5) The future social care workers training has a range of contradictions that can be overcome with the help of complex approach from both state regulation and updating context, forms, means and methods of managing higher educational establishments. The scientific development of the issue concerning the future social care workers training of formation of healthcare experience of pre-schoolers, making it one of the major courses of modern pedagogical beliefs and educational practice are actualized above.